Effects of ovarian endometriotic fluid exposure on fertilization rate of mouse oocytes and subsequent embryo development - Piromlertamorn Waraporn; Saeng-anan Ubol; Vutyavanich Teraporn (BMC, 2013)
Abstract Background Accidental exposure of oocyte/cumulus complex to endometriotic fluid is not uncommon during oocyte retrieval. Only two studies were available on this subject and they gave conflicting results. In this study, we used a mouse model to evaluate the effect of controlled exposure of oocytes to ovarian endometriotic fluid. Methods Mouse oocytes/cumulus complexes (n = 862) were divided into 4 groups, and were exposed to endometriotic fluid (group 1), pooled sera from subjects without endometrioma (group 2), phosphate-buffered saline (group 3), and fertilization medium (controls). After five minutes, oocytes were washed and inseminated. Embryo development was observed daily. The quality of hatching blastocysts was assessed by counting the number of inner cell mass (ICM) and trophectoderm (TE) cells. Results The fertilization, cleavage and blastocyst formation rates in the four groups were not statistically different. The proportions of hatching/hatched blastocysts from fertilized oocytes in groups 1 and 2 were significantly lower than those in group 3 and controls (P = 0.015). Hatching blastocysts from all groups showed no significant difference in the number of ICM and TE cells. Conclusions Exposure of mouse oocytes/cumulus complexes to endometriotic fluid had subtle detrimental effects on subsequent blastocyst development. However, one should be cautious in projecting the results of this study to contaminated human oocytes in a clinical setting.